Hubungan Pengetahuan dan Dukungan Keluarga Dalam Kepatuhan Pembatasan Asupan Cairan Pasien Hemodialisa Di RSBT Pangkalpinang - Rima Berti Anggraini; Rezka Nurvinanda (Fakultas Ilmu Kesehatan Universitas Katolik Musi Charitas, 2021)
Compliance with fluid intake restriction is one of the problems in chronic kodney failure patients undergoing hemodialisysis. The difficulty of limiting fluid intake in patiens undergoing hemodialysis is due orance and lack of support from the family so that fluid intake is not controlled in patients with chronic kidney failure. This of course will worsen the patient’s health condition. Purpose of this research is to know the related factors towards the obedience in limiting fluid intake on the patients receiving hemodialysis at Bakti Timah Hospital Pangkalpinang. Method This research employs a Cross-sectional design. The sample of this research is the entire kidney failure patients receiving hemodialysis therapy with the total number of 66. The data are collected using questionnaire and measuring body weights based on Inter Dialytic Weight Gain. The data are then analyzed using Chi Square Test. Result The result of this research shows that there are relation factors toward the obedience in limiting fluid intake on the patients receiving hemodialysis are knowledge (p=0.034), and family support (p=0.027).The most dominant factor is the family support with the score of (POR=3.571). Conclusion There is a significant relationship between knowledge and family support in limiting fluid intake, so very important to improve education and counseling in hemodialysis patient